The importance of affectivity in the Occupational Therapy teaching pratice (Research, Society and Development, 2019)
Due to the relevance of the affectivity in the subject interrelationship, its role in the relationship must be considered between students and teachers. In this way this study has as objective demonstrate research data about the importance of the affectivity for the Occupational Therapy teachers. For this, a qualitative, empirical and exploratory research was carried out in two universities in Rio Grande do Sul with six Occupational Therapy professors. The teacher statements were analyzed in categories according to the content, this allowed to verify that the principles of affectivity, so important for the knowledge mediation and in teaching interpersonal relationships, are common to their professional practices. Is expected that this research stimulate the reflection about affectivity in higher education teaching and learning relations.